Prevalence of celiac disease in systemic lupus erythematosus, sjogren syndrome and systemic sclerosis: A systematic review and meta-analysis - Beas, Renato (2024)
Background: Celiac disease (CeD) is an immune-mediated disorder affecting the small bowel, associated with genetic factors and increasing global prevalence. Aim: This study explores the association between CeD, Systemic Lupus Erythematosus (SLE), primary Sjogren syndrome (pSS), and Systemic Sclerosis (SSc). Methods: A systematic review and meta-analysis were conducted following PRISMA guidelines. Searches across multiple databases yielded 2728 articles, with 15 studies selected. Data extraction included study characteristics, prevalence of CeD and CeD antibodies in SLE, pSS, and SSc. Quality assessment utilized the Newcastle-Ottawa Scale. Results: The meta-analysis revealed a pooled prevalence of biopsy-proven CeD in SLE, pSS, and SSc of approximately 3%. Seroprevalence of any CeD antibody in SLE, pSS, and SSc ranged from 3% to 10%. Notably, pSS exhibited the highest prevalence at 5.59%. High heterogeneity was observed in seroprevalence across autoimmune conditions. Quality assessment indicated robust methodological quality in the selected studies. Conclusion: This study highlights a significantly higher prevalence of CeD, especially pSS, compared to the general population. The findings underscore the importance of recognizing elevated CeD antibodies in patients with SLE, pSS and SSc emphasizing the need for early detection and comprehensive care for gastrointestinal symptoms in these conditions.